Inclusive Education in Punjab: Challenges and Way Forward - Abbas, Fazal; Thakur, Ibtasam (JIE, 2023)
The study was carried out to explore (i) the challenges faced by Punjab Government in implementing Inclusive Education; (ii) to what extent Punjab Government has been successful in bringing parity in education system by employing inclusive education. Relevant literature and articles of renowned scholars were studied. Structured interviews with inclusive education experts and concerned professionals were carried out. Result reveals that a number of initiatives were taken by Punjab Government but challenges are proportionately much grave hindering its effective implementation. It is recommended that the Department of Special Education should upscale its implementing strategy and advocacy needs in line with the provisions of the national education policy so as to develop a road map for bringing inclusive education into the education system. Required instructional material should be provided within the schools. If schools are not equipped with requisite material, teachers would not be able to perform their duty properly. A meaningful coordination between general and special education can bring positive results in terms of planning and implementing inclusive education in a time bound strategic framework. General and Special education Departments need to have to actively undertake a joint review of the current curriculum and collaborate with relevant university departments in this arduous task.